Educational and research utility of the registrar clinical encounters in training (ReCEnT) project: an exploration of mechanisms using the context, input, process and product (CIPP) framework - Parker Magin; Andrew Davey; Michael Tran; Susan Wearne (Family Medicine and Community Health, 2025)
Background The Registrar Clinical Encounters in Training (ReCEnT) project is an Australian general practice vocational training programme with integrated and interdependent education and research functions. Trainees (registrars) contemporaneously document in-consultation clinical experience and actions.Objectives Using a realist lens, we elucidate the mechanisms underpinning project outcomes to answer questions around programme effectiveness, impacts, sustainability and the lessons and findings that are translatable to other primary care training programmes.Methods The context, input, process and product framework was used. As a means to understand the interactions between each of the interdependent components, it allows for inferences regarding causal mechanisms for specific outcomes.Results Context: ReCEnT occurs within an apprenticeship-like model of general practice vocational training entailing a central supervisor/apprentice relationship. ReCEnT has demystified the content and characteristics of registrar consultations. Input: multiple stakeholder involvement is both advantageous and a logistical challenge, with the programme’s success dependent on registrars, practices and training providers providing detailed and accurate data, with prompt subsequent processing. Process: contemporaneous consultation data collection in different stages of training constitutes a component of registrars’ programmatic assessment. Product: individualised feedback provides educational benefit through reflection. Clinical and educational research questions can be addressed with resulting research translation feeding back into the programme model and government policy. Clinical behaviour change is also evaluated.Conclusion ReCEnT is unique, globally, in its scope and longevity (2010–present). Creation of meaningful, individualised feedback facilitates reflection and provides both immediate educational benefits and the substrate for further research, programme and policy design and targeted formal teaching and learning.